Analisis Komparasi Biaya Distribusi Sistem Reorder Point dan Distribution Resource Planning - Nina Tania (Jurnal Teknik Industri, 2007)
Distribution method of Reorder Point is method which controlling and observing the amount of Inventory pursuant to at boundary of Reorder Point. If inventory smaller than boundary of reorder point hence require to do/conduct order. Method of Distribution Resource Planning is method which controlling and observing the amount of inventory pursuant to at stock safety. Where if inventory less than stock safety hence require to do/conduct order as according to time lead. Each;Every company will be out for always always menu request of consumer when and correct amount. For that fluency in pendistribution of product have to be majored so that require to be done/conducted by an Schedule Mains Distribution good JID as according to requirement each;every existing distribution network level. In this research of writer try to compare the expense of released distribution with method of DRP and Method of Reorder Point. Where distribution system at PT. PAI Probolinggo use Method of Reorder Point. In the reality after its it him Method distribution of DRP the expense of compared to smaller distribution of Method of Reorder Point. With applying of DRP can cost effective equal to that is equal to Rp. 1823171.4 or 14.7386369 % from expense of before using Reorder Point.